Reagent and analyte ion hydrates in secondary electrospray ionization mass spectrometry (SESI-MS), their equilibrium distributions and dehydration in an ion transfer capillary: Modelling and experiments - Dryahina, Kseniya; Som, Suman; Smith, David; Španěl, Patrik (Rapid communications in mass spectrometry, 2021)
RATIONALE: Secondary electrospray ionization (SESI) in a water spray environment at atmospheric pressure involves the reactions of hydrated hydronium reagent ions, H3 O+ (H2 O)n , with trace analyte compounds in air samples. Understanding the formation and dehydration of reagent and analyte ions is the foundation for meaningful quantification of trace compounds by SESI-mass spectrometry (MS). METHODS: A numerical model based on gas-phase ion thermochemistry is developed that describes equilibria in H3 O+ (H2 O)n reagent cluster ion distributions and ligand switching reactions with polar NH3 molecules leading to equilibrated hydrated ammonium ions NH4 + (H2 O)m . The model predictions are compared with experimental results obtained using a cylindrical SESI source coupled to an ion-trap mass spectrometer via a heated ion transfer capillary. Non-polar isoprene, C5 H8 , was used to further probe the nature of the reagent ions. RESULTS: Equilibrium distributions of H3 O+ (H2 O)n ions and their reactions with NH3 molecules have been characterized by the model in the near-atmospheric pressure SESI source. NH3 analyte molecules displace H2 O ligands from the H3 O+ (H2 O)n ions at the collisional rate forming NH4 + (H2 O)m ions, which travel through the heated ion transfer capillary losing H2 O molecules. The data for variable NH3 concentrations match the model predictions and the C5 H8 test substantiates the notion of dehydration in the heated capillary. CONCLUSIONS: Large cluster ions formed in the SESI region are dehydrated to H3 O+ (H2 O)1,2,3 and NH4 + (H2 O)1,2 while passing through the heated capillary, and considerable diffusion losses also occur. This phenomenon is also predicted for other polar analyte molecules, A, that can undergo similar switching reactions, thus forming AH+ and AH+ (H2 O)m analyte ions.